An investigation on the mitigation of end-stop impacts in a magnetorheological damper operated by the mixed mode - Yazid, I. I. M. (Institute of Physics Publishing, 2016)
This paper presents mitigation behaviour of magnetorheological (MR) damper operated with a mixed working modes. A combination of the shear and squeeze modes is employed in the structure of MR damper to obtain the field-dependent normal yield stress as well as strengthen the squeeze effect. The experimental evaluation shows that when the piston is squeezing the bottom gap from the stroke of 25 to 26 mm, the sudden increase of squeeze force is observed confirming the existence of the mitigation effect. It is also observed that the magnitude of mitigation force is positively correlated with the magnitude of current given to the electromagnet. The measured peak mitigation forces are ranged from 722 N to 1032 N when the electromagnet currents are varied from 0.2 A to 0.8 A, respectively. The variable mitigation effect indicates that the concept can be further discussed as a potential impact protection feature in an MR damper.